Outlining Community Perceptions of Climate Change in Local Adaptation Strategies Development: The Case of ClimAdaPT.Local - Schmidt, Luísa (2018)
ClimAdaPT.Local’s goal was the development of 26 Municipal Adaptation Strategies for Climate Change (EMAAC). The project aimed to increase the capacity of these municipalities to incorporate adaptation to Climate Change (CC) in their planning instruments. To do so, several methodologies and tools were specifically developed. One of these, the local stakeholder engagement strategy, constitutes an innovation as far as the development of these strategies in Portugal is concerned. This paper focuses on this stakeholder engagement process and its achievements. ClimAdaPT.Local’s stakeholder engagement was workshop based. These were put in place in order to understand perceptions of CC, its impacts, local risks, but also survey potential inputs into the ongoing EMAAC development. Each session comprised several discussion tables, intending to: (i) obtain a global reference framework on perceptions and sensitivity to CC at the local level; (ii) complement the vulnerabilities assessment made by the technical﻿ staff from each municipality; (iii) inform, adjust and optimise the local adaptation strategies. In addition, stakeholders were asked to share their visions of the future, namely how CC and local territorial identity will be articulated in the near, and not so near, future. The analytical findings encompassed in paper refer to point (i). All in all, in Portugal, there is a widespread perception that CC is happening, in particular among social groups that engage in activities such as agriculture and fishing. And despite being considered to pose a threat, CC is, at the same time, broadly perceived as a window of opportunity to put in place measures that improve local living conditions.